2019
DOI: 10.1088/1742-6596/1217/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phenolic acid from ethanol extract leaves binahong (Anredera cordifolia (ten) stennis) and antioxidant activity test

Abstract: Binahong (Anredera cordifolia (Ten.) Stennis) is a plant which comes from Basellaceae family. Also, this plant is also known to have biological activity due to the presence of the bioactive compound. Phenolic acids are bioactive compound and widely used as antioxidants. Identification and testing of antioxidant activity using ethanol extract have been done in this research. Phenolic acids were isolated without hydrolysis (TH fraction), and by acid hydrolysis (fraction HA), and alkaline hydrolysis (HB fraction)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“… 24 27 The phenolic acid found in Binahong leaf extract is P-coumaric acid, and the triterpenes found are ursolic acid and oleanolic acid. 24 , 28 A few studies have been conducted to observe the effects of Binahong leaf extract on wound healing. Hanafiah et al showed that Binahong leaf extract could increase the proliferation of NIH-3T3 fibroblasts and also proved that 3% Binahong leaf extract gel could accelerate palatal mucosal wound healing in rats by increasing the proliferation of fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“… 24 27 The phenolic acid found in Binahong leaf extract is P-coumaric acid, and the triterpenes found are ursolic acid and oleanolic acid. 24 , 28 A few studies have been conducted to observe the effects of Binahong leaf extract on wound healing. Hanafiah et al showed that Binahong leaf extract could increase the proliferation of NIH-3T3 fibroblasts and also proved that 3% Binahong leaf extract gel could accelerate palatal mucosal wound healing in rats by increasing the proliferation of fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Oleic acid, eicosyl ester is a monounsaturated omega-9 fatty acid, that has been reported for having mosquito repellent activity (Gurunathan et al, 2016). The FT-IR spectrum depicted a large parabola-shaped peak observed at 3184 cm -1 with aromatic C-H stretching, vibrations, with weak intensity representing the presence of Coumaric acid, aliphatic compounds (Fachriyah et al, 2019). However, alkane stretching indicated the presence of steroids, tannins, saponins.…”
Section: Resultsmentioning
confidence: 94%
“…Cholestan-3-ol has already been reported in Canscora perfoliata Lam. (Gentianaceae) property and showed the highest cytotoxicity against A549 lung cancer cells in vitro and in vivo (Pan et al, 2016;Fachriyah et al, 2019). Studies have demonstrated the cytotoxic effect of thiophenes.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical screening results from binahong showed alkaloids, flavonoids, triterpenoid, steroid, phenolic acid, glycoside, saponin, and tannin content. Alkaloid (betanidine) and phenolic acid (pcoumaric acid) compounds were found in ethanolic extract of binahong leaves [12]. Flavonoids from the ethyl acetate extract of binahong leaves was identified 3,5,3',4'-tetrahydroxiflavonol and from ethanol extract was identified as 8-glucopyranosyl-4',5,7-trihydroxyflavone (orientoside) that can be used as antidiabetic [13].…”
Section: Introductionmentioning
confidence: 99%